Factors influencing the initiation of estrous cycles and expression of estrus in beef cows - Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2000)
Body condition, parity, and days postpartum at the onset of the breeding season determine the proportion of cows that initiated first postpartum ovarian activity and ovulated before the start of the breeding season. Hormonal treatments that included both GnRH and a source of progestin enhanced expression of estrus and led to greater pregnancy rates of suckled beef cows.
Keywords: Cattlemen& #x27; s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Suckled cows; Body condition; Parity; Postpartum; Estrus